The concept of sustainable marketing in the presence of Bulgarian activity - Dimova, Nadezhda (Leadership, Society, Strategic Visions, 2021)
The dynamic business environment changes and imposes the emergence of different forms of marketing, transforms demand and supply, modifi es consumer behavior itself. Managers at different corporate levels face a number of challenges to address these changes and respond to the ever-increasing pressures of technology, and in particular, digitization in all areas of life. The development of sustainable marketing is a kind of response to any changes that include even those on the planet as a whole. Wonderful and worthy of respect is the example given by Bulgarian companies or those that enter the Bulgarian market.